(untitled) (Conferencea, 2022)
Vitamin B12 is a co-enzyme of two important reactions: 1) the formation of succinic acid from fatty acids and amino acids; 2) the formation of homocysteine and methionine, which are necessary for the synthesis of choline, phosphatidylcholine, as well as adrenaline, creatine and carnitine. In addition, during the second reaction, folic acid is retained in the cell and thus adequate nucleic acid synthesis is ensured. Vitamin B12 deficiency is biochemically accompanied by an increase in the level of methylmalonic acid (MMK) and homocysteine, and a decrease in the level of methionine and folic acid. Clinically, vitamin B12 deficiency is manifested by megaloblastic anemia, funicular myelosis, distal paresthesias, increased tendon reflexes, the appearance of ataxia, disorientation, hallucinations and memory impairment . Vitamin B12 deficiency and its accompanying hyperhomocysteinemia and elevated levels of methylmalonic acid cause sensory polyneuropathy, very similar to diabetic neuropathy. Patients with concomitant vitamin B12 deficiency have also been noted to worsen the course of diabetic neuropathy. On the other hand, prolonged use of Metformin is associated with the development of vitamin B12 deficiency. The aim of our study was to investigate the relationship of clinical manifestations of diabetic polyneuropathy with vitamin B12 levels in patients with type 2 diabetes mellitus.